2023
DOI: 10.1021/acsanm.3c02464
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared/pH Dual-Responsive Nanosponges Encapsulating Gold Nanorods for Synergistic Chemo-phototherapy of Lung Cancer

Maryam Deinavizadeh,
Ali Reza Kiasat,
Nasrin Hooshmand
et al.

Abstract: Combined chemo-photothermal therapy (CT-PTT) based on gold nanorods (AuNRs) loaded with chemotherapies has been recently introduced as a promising anticancer therapy with relatively lower side effects and higher efficacy over individual therapeutic approaches. We fabricated β-cyclodextrin-based nanosponges encapsulating PEGylated gold nanorods and doxorubicin (DOX), AuNR-S-PEG.β-CD NS-DOX, comprehensively characterized it using TEM, SEM, FE-SEM, FITR, and DLS and then evaluated it for CT-PTT versus the respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…[67][68][69] In one study, Deinavizadeh et al demonstrated combined photothermal chemotherapy based on NIR-responsive gold nanorod (AuNR)-functionalized b-cyclodextrin nanosponges. 70 PEGylated gold nanorods were encapsulated in the pores of bcyclodextrin-based nanosponges (b-CD NS) to prepare the AuNR-S-PEG.b-CD NS nanocomposite for further loading of DOX molecules. The maximum drug loading efficiency was found to be 35 wt%.…”
Section: Metal Nanomaterialsmentioning
confidence: 99%
“…[67][68][69] In one study, Deinavizadeh et al demonstrated combined photothermal chemotherapy based on NIR-responsive gold nanorod (AuNR)-functionalized b-cyclodextrin nanosponges. 70 PEGylated gold nanorods were encapsulated in the pores of bcyclodextrin-based nanosponges (b-CD NS) to prepare the AuNR-S-PEG.b-CD NS nanocomposite for further loading of DOX molecules. The maximum drug loading efficiency was found to be 35 wt%.…”
Section: Metal Nanomaterialsmentioning
confidence: 99%